PENGARUH KETERAMPILAN UPAH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. INDUSTRI KARET NUSANTARA MEDAN - Hamonangan, Albon; Lubis, Zulkarnain; Rahman, Abdul (JURNAL AGRICA, 2015)
Each company will always strive to be have human resources fully engaged to effort of produce high productivity and achieve those objectives. This study aimed to determine the effect of skills, wages, motivation and work environment on employee productivity PT.Industri Karet Nusantara, and to find out how much each of these factors can affect employee productivity. PT.Industri Karet Nusantara have 45 employees at the same time as the sample population in this study. Data was collected using methods questionnaire and subsequent observations, further descriptively analyze . The results showed that the skills, wages, motivation, and work environment has an influence on Productivity of employees at PT. Industri Karet Nusantara Medan. Contribution of these factors can affect the productivity of employees by 73,2% and 26,8%  influenced by other factors that are not revealed in this study. Keywords : Work produktivity, Skill, Motivation, Wages and Working environment